2009
DOI: 10.1002/esp.1760
|View full text |Cite
|
Sign up to set email alerts
|

Modelling hyperconcentrated flow in the Yellow River

Abstract: A large amount of the total sediment load in the Chinese Yellow River is transported during hyperconcentrated floods. These floods are characterized by very high suspended sediment concentrations and rapid morphological changes with alternating sedimentation and erosion in the main channel, and persistent sedimentation on the floodplain. However, the physical mechanisms driving these hyperconcentrated floods are still poorly understood. Numerical modelling experiments of these floods reveal that sedimentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 29 publications
0
30
0
1
Order By: Relevance
“…In that case, 蟽 t should be closer to 2. In a model with comparable vertical resolution as applied here, the observed sediment-induced stratification effects during hyperconcentrated floods could only be reproduced using a Prandtl-Schmidt number of 2 (van Maren et al 2009). …”
Section: Hydraulic Dragmentioning
confidence: 90%
See 1 more Smart Citation
“…In that case, 蟽 t should be closer to 2. In a model with comparable vertical resolution as applied here, the observed sediment-induced stratification effects during hyperconcentrated floods could only be reproduced using a Prandtl-Schmidt number of 2 (van Maren et al 2009). …”
Section: Hydraulic Dragmentioning
confidence: 90%
“…Previous work showed that this term is essential to capture the suspended sediment dynamics in high-concentration environments (Winterwerp and van Kessel 2003;van Maren 2007;van Maren et al 2009). However, in this study, the sedimentinduced density effects only limitedly influenced the hydrodynamics and sediment dynamics.…”
Section: Hydraulic Dragmentioning
confidence: 99%
“…Determining when a flow is hyperconcentrated is not straightforward because hyperconcentrated flow has not been properly defined until now (Qian et al 1979;Wang 1996;Jiao 2004). It is usually classified based on the magnitude of C value (van Maren et al 2009). In the study area, Xu (1999aXu ( , 2002 gave a threshold C of 300 kg m -3 .…”
Section: The Development Of Hyperconcentrated Flowmentioning
confidence: 99%
“…However, at such concentrations, the fall velocity decreases due to hindered settling, therefore leading to a more uniform distribution of sediment over the water column and reducing stratification. This phenomenon has for example been observed in the Yellow River (Van Maren et al 2009). …”
Section: Extension To Tidal Flowsmentioning
confidence: 66%
“…, with 蟽 蟻 = 2 (Van Maren et al 2009). At the bed, sediment deposits at a rate D and erodes at rate E, which are described by…”
Section: Model Equationsmentioning
confidence: 99%